Adherence to a healthy lifestyle in association with female infertility risk: the mediating role of uric acid - Huang, Zhihui; Yang, Ziqi; King, Lei; Chen, Hong; Wan, Xinxia; Luo, Qimei; Hu, Rili; Peng, Lin; Zhao, Yan; Huang, Jialyu (Frontiers in Nutrition, 2025)
BackgroundInfertility poses a significant health challenge for reproductive-aged women globally and could be shaped by both genetic risks and lifestyle factors. Existing studies predominantly focus on individual lifestyle components, while their joint effect on infertility remains limited.MethodsThis large cross-sectional study analyzed data from 2,067 women aged 18–44 years, sourced from the National Health and Nutrition Examination Survey spanning 2013 to 2020. Six modifiable healthy lifestyle factors were included: current non-tobacco smoking, non-excessive alcohol drinking (1–14 g/day), sufficient physical activity (≥150 min/week), healthy diet (top 40% of Healthy Eating Index-2015 score), optimal waist circumference (<80 cm), and adequate sleep duration (7–9 h/day). Participants received 1 point for each factor (scale 0 to 6). Infertility status was self-reported in reproductive health questionnaire. Multivariable regression, stratified, sensitivity, and mediation analyses were performed. External validation was conducted on another 33,881 women enrolled from an academic reproductive medicine center in China from January 2014 to December 2022.ResultsAfter adjusting for potential covariates, women with 5–6 healthy lifestyle factors exhibited a 70% lower risk of infertility (OR: 0.30, 95% CI: 0.17–0.52) compared to those with 0–1 factor. A 22% reduction in infertility risk was observed with each additional healthy lifestyle factor (OR: 0.78, 95% CI: 0.70–0.88). The association was more pronounced in those aged <30 years (P-interaction<0.001) and females who had never been pregnant (P-interaction = 0.01). Current nonsmoking and optimal waist circumference were identified as the most pivotal determinants among six factors. Additionally, serum uric acid was estimated to mediate 9.61% (95% CI: 3.93 to 21.88%) of the inverse relationship between the composite healthy lifestyle score and infertility. Serum uric acid levels were also confirmed to be positively associated with female infertility risk in real-world data analysis.ConclusionOur study highlights the inverse association between adherence to a healthy lifestyle and female infertility via uric acid mediation. These findings provide supporting evidence that comprehensive lifestyle modification may be an effective, low-cost strategy for managing infertility.